Taller de Procesamiento de Lengua de Señas Peruana - (:unkn) unknown (My University, 2026)
This funding will help organize the first Peruvian Sign Language Processing (LSP) Workshop. Our goal through this workshop is to train members of the Peruvian Deaf Community on topics such as technology for the deaf and hard of hearing and analysis of gra